PENILAIAN MEDIA PEMBELAJARAN E-MODUL MATERI KERAH KEMEJA - Melinda Lasaret, Putri; Suryawati, Suryawati (Practice of Fashion and Textile Education Journal, 2022)
This study aims to create e-module in men's shirt collar material and to conduct the feasibility evaluation of e-module learning media in men's shirt collar material. The research evaluation was carried out by a panel of material and media experts. The research methodology used pre-experimental (one-shot case study). Research created e-module learning media that combines component such as layout, texts, audio, images, and videos using the Flip PDF Professional application assisted by CorelDRAW and Adobe Premiere Pro. E-module learning media in this men's shirt collar material has been declared very feasible based on aspects of content feasibility, linguistic aspects, presentation aspects, graphic aspects, software engineering aspects, visual communication aspects, stand alone aspects, and adaptive aspects. The results obtained for the assessment of learning media for material aspects are 88.04%, and media aspects are 82.4%, so in general the e-module learning media for men’s shirt collar material has been declared very feasible. So that e-module learning media that the researchers arranged can be used as a learning media and students can study independently.